2014
DOI: 10.1007/s00066-014-0755-5
|View full text |Cite
|
Sign up to set email alerts
|

How nescience may obscure evidence

Abstract: limitations of the study were recognized and let to some critical comments [7], current guidelines [8,14] rapidly adopted the omission of ALND in these selected patients.Unreckoned insights about the quality of evidence generated by the Z0011-trial were provided by a recent publication on behalf of the Alliance for Clinical Trials in Oncology by Jagsi et al. Briefly, the study [3] (published in 2011) comprised 891 women from 115 institutions with a clinically negative axilla who underwent sentinel node dissect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…However, the study has substantial methodological weaknesses: recruitment was interrupted prematurely, and a total of 103 patients could not be analyzed. In violation of the explicit protocol requirements, additional RNI was carried out in around 15 % of them [21,22], With regard to the prognosis when there is sentinel node involvement, a countertrend emerged in a subgroup analysis in the NSABP-B-32 study [23]. Fifteen percent of the lymph nodes initially evaluated as histopathologically negative were found to have occult LN metastases at an additional histological examination.…”
Section: Radiotherapy Of the Internal Mammary Nodes (Imns)mentioning
confidence: 99%
“…However, the study has substantial methodological weaknesses: recruitment was interrupted prematurely, and a total of 103 patients could not be analyzed. In violation of the explicit protocol requirements, additional RNI was carried out in around 15 % of them [21,22], With regard to the prognosis when there is sentinel node involvement, a countertrend emerged in a subgroup analysis in the NSABP-B-32 study [23]. Fifteen percent of the lymph nodes initially evaluated as histopathologically negative were found to have occult LN metastases at an additional histological examination.…”
Section: Radiotherapy Of the Internal Mammary Nodes (Imns)mentioning
confidence: 99%
“…The Early Breast Cancer Trialists’ Collaborative Group analysis revealed a 10-year risk of an isolated locoregional recurrence as the first event after mastectomy of 20.3 % for patients with 1–3 positive axillary lymph nodes, and of 32.1 % for patients with ≥ 4 positive nodes. The addition of radiotherapy significantly reduced the risk to 3.8 and 13 %, respectively [ 2 , 49 , 50 ]. In cohorts treated with modern systemic therapies, the total locoregional recurrence rate is substantially lower; however, the relative risk reduction after radiotherapy remains unchanged [ 51 ].…”
Section: Treatment Of Local Recurrence After Mastectomymentioning
confidence: 99%
“…The Early Breast Cancer Trialists' Collaborative Group analysis revealed a 10-year risk of an isolated locoregional recurrence as the first event after mastectomy of 20.3% for patients with 1-3 positive axillary lymph nodes, and of 32.1% for patients with 4 or more positive nodes. The addition of radiotherapy significantly reduced the risk to 3.8 and 13%, respectively [2,44,45,46]. In a retrospective study, Katz et al [47] reported on the local recurrence patterns of 1,031 women treated in 5 prospective trials with mastectomy and adjuvant chemotherapy without radiation therapy.…”
Section: Therapy Of Isolated Locoregional Recurrences After Mastectomymentioning
confidence: 99%